EXHIBITION INDUSTRY: CURRENT ECONOMIC TRENDS AND PROSPECTS OF THE FUTURE - Головня, Олена (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The purpose of the study is to assess current economic trends and prospects for future development of the exhibition industry. The theoretical and methodological basis of the study were the scientific works of domestic and foreign authors on the financing of social development through innovative technologies, Internet resources. The study used a set of general and special scientific methods and approaches, including: monographic - in the literature review of the research problem; system and structural analysis - in the interpretation of the essence of virtual exhibitions, webinar exhibitions, hybrid exhibitions as the latest forms of exhibition activities; method of processing and analysis of survey results to determine the most influential factors in the intensification of exhibition activities in the world; method of logical generalization, system method, method of comparisons, which allowed to ensure the conceptual unity of the study. The author determined that the exhibition industry, together with the wider Live Event Community (MICE), was the first to be affected by the quarantine requirements for the cancellation of events and the complete closure of the business. It has been studied that virtual events currently perform an important substitution function, but are sometimes much less effective than real exhibitions. The author argues that in modern conditions, exhibition organizers use different types of information technology that improve the efficiency of event management, collect, store and structure information received by participants and organizers, reduce the cost of exhibition events. Among the newest types of exhibition events are researched: virtual exhibitions, webinar exhibitions, hybrid exhibitions. For further long-term development of the exhibition industry it is necessary to finance relevant information programs, find partners, invest in digital proposals.